DIURNAL VARIATION IN THE CATCHES OF SILVERBELLIES IN PALK BAY - Venkataraman, G; Badrudeen, M (Indian Journal of Fisheries, 2011)
5\ comparison of the trawl landings from Palk Bay by day and nightfishing showed a marked variation in the catches of silverbellies between the two.Another interesting feature noted was that even in night fishing, usually highercatches of silverbellies were observed on full moon nights than on new moonnights both in Palk Bay and Gulf of Mannar. From an analysis of the sizegroups of Leiognathus jonesi and L. brevirostris caught, it was seen that the proportionof smaller size group was greater in the night catches than in the daycatches whereas the proportion of the larger size group was greater in the daycatches than in the night catches. The diurnal variation in the catches of silverbelliesshows that they stay at the bottom during day time and at nights goodmany of them migrate from there and rise to surface and sub-surface waters. Thisand the instances of sharp difference in the catch rates observed between fullmoon and new moon nights indicate a close link between light and the processof migration in silverbellies. The probable cause for the variation in the sizegroups in the catches by day and night fishing is pointed out. Fishing at thesurface, sub-surface and midwater levels at night by using suitable gear is suggestedfor augmenting the production of silverbellies.